Comparison of auditory cueing in toe tapping and gait in persons with Parkinson’s disease - Stegemöller, Elizabeth L.; Berg, Riley; Warnecke, Alison; Hammer, Mollie (Frontiers in Human Neuroscience, 2023)
Much research has examined the relationship between bradykinesia and gait impairment in persons with Parkinson's disease (PD). Specifically, impairments in repetitive movements of the upper extremity have been associated with freezing of gait. Studies examining lower extremity repetitive movements are limited. Moreover, the use of external cueing has been a treatment strategy for both bradykinesia and gait, but information on how cues should be used is lacking.The purpose of this study was to compare the effects of auditory cueing on one side versus both sides for bilateral repetitive toe tapping and gait, and to determine if there was a relationship between toe tapping and gait. We hypothesize that there will be no difference between the cueing conditions, but that there will be a significant association between repetitive toe tapping performance and gait performance. Twenty-seven persons with PD completed a toe tapping task in which the more affected side was cued at 70 beats per minute (BPM), the less affected side was cued at 70 BPM, and both sides were cued at 140 BPM. The same cueing conditions were completed for the gait task. Inter movement interval and amplitude data was collected and analyzed for the toe tapping task. Stance time, swing time, step length, and step width were collected and analyzed for the gait task. Results revealed a significant difference in movement performance between the single side cueing conditions and both sides cued condition for inter movement interval (toe tapping), stance time (gait), step length (gait), and step width (gait).Moreover, results revealed a significant association between inter movement interval and stance time and step length. This would suggest that cueing both sides is better than only one side and that there is a relationship between toe tapping and gait performance when both sides are cued in persons with PD. This study adds to the literature exploring possible shared mechanisms between bradykinesia and gait in persons with PD.